Changes in Serum Testosterone and Adrenal Androgen Levels in Transgender Women With and Without Gonadectomy - Collet, Sarah; Gieles, Noor C; Wiepjes, Chantal M; Heijboer, Annemieke C; Reyns, Tim; Fiers, Tom; Lapauw, Bruno; den Heijer, Martin; T'Sjoen, Guy (The journal of clinical endocrinology and metabolism, 2023)
BackgroundInitiating feminizing gender-affirming hormone therapy (GAHT) in transgender women causes a steep decline in serum testosterone. It is unknown if testosterone concentrations change further and whether adrenal androgen levels change during feminizing GAHT and after gonadectomy. This limits clinical decision making in transgender women with symptoms attributed to GAHT or gonadectomy. MethodsTransgender women (n = 275) initiating estradiol and cyproterone acetate (CPA) were included at baseline, and had follow-up visits after 3 months, 12 months, and 2 to 4 years. During follow-up, 49.5% of transgender women underwent a gonadectomy. Total testosterone (TT), dehydroepiandrosterone (DHEA), dehydroepiandrosterone sulfate (DHEAS), and androstenedione (A4) were measured using liquid chromatography tandem mass spectrometry. ResultsAfter 3 months of GAHT, mean TT, calculated free testosterone (cFT), and A4 decreased by 18.4 nmol/L (95% CI, −19.4 to −17.4, P < 0.001 [ie, −97.1%]), 383 pmol/L (95% CI, −405 to −362, P < 0.001 [ie, −98.3%]), and 1.2 nmol/L (95% CI, −1.4 to −1.0, P < 0.001 [ie, −36.5%]), respectively, and remained stable thereafter. DHEA and DHEAS decreased by 7.4 nmol/L (95% CI, −9.7 to −5.1 [ie, −28.0%]) and 1.8 µmol/L (95% CI, −2.2 to −1.4 [ie, −20.1%]), respectively, after 1 year and did not change thereafter. After gonadectomy, CPA therapy is stopped, which induced no further change in TT, cFT, DHEA, DHEAS, and A4 compared with those who did not undergo gonadectomy. ConclusionsOur findings confirm that after an initial drop, testosterone levels in transgender women remain stable. Adrenal androgens decrease in the first year of CPA and estrogen supplementation and remain unchanged after gonadectomy. Androgens did not change after gonadectomy and cessation of CPA. Correlates with clinical symptoms remain to be elucidated.